2022
DOI: 10.3390/ijerph19084610
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Satisfaction with Solid Waste Management Services: A Central–Local Comparison in China

Abstract: The Chinese central government proclaimed a mandatory or demonstration waste separation policy in some cities or counties to manage the increasing amounts of generated waste since 2017. Many cities and regions have also begun to build waste separation management systems and institutions, and community managers have created waste management rules and provided separation management services under the guidance of local government. However, little is known about how these policies or services have performed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Respondents using ‘Door-to-door collection plus Storing’ or ‘Sorting’ methods reported lower satisfaction levels, possibly because (1) they are not happy with the frequency/timing or even the attitude of the waste collectors, (2) by opting for a more environmentally friendly option of putting their waste in the government-installed facilities, they feel that even though they try to contribute their share by bringing the waste to public waste facilities, the government-provided WDMS is still lagging. These results align with the findings of [ 90 ], Table A3, which showed that ‘waste separation behavior’ in some areas can lower residents’ satisfaction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respondents using ‘Door-to-door collection plus Storing’ or ‘Sorting’ methods reported lower satisfaction levels, possibly because (1) they are not happy with the frequency/timing or even the attitude of the waste collectors, (2) by opting for a more environmentally friendly option of putting their waste in the government-installed facilities, they feel that even though they try to contribute their share by bringing the waste to public waste facilities, the government-provided WDMS is still lagging. These results align with the findings of [ 90 ], Table A3, which showed that ‘waste separation behavior’ in some areas can lower residents’ satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Paying a fee for the waste management infrastructure is negatively associated with users’ satisfaction. The results are similar to the findings of [ 90 ] but opposite to those of [ 91 ]. This finding can be related to the post-purchase process, where the payees are less satisfied than the respondents who do not pay.…”
Section: Discussionsupporting
confidence: 81%
“…Self-efficacy explains a large part of entrepreneurial potential, such as motivation, opportunities, and resources. Creative self-efficacy moderates the relationship between entrepreneurial education experience and innovative behavior, suggesting that higher creative self-efficacy strengthens the relationship between education and innovation behavior (Wang et al, 2022). Self-efficacy can create a positive relationship between entrepreneurial alertness and social entrepreneurial intentions (Urban, 2020).…”
Section: Self Efficacymentioning
confidence: 99%
“…In 2022 Aiqin Wang et al, (Wang et al, 2022) The search returned 476, 878, and 374 results. The findings offered some hope for the adoption and implementation of CE by highlighting key indicators and facilitators, but they also revealed some challenges, including insufficient funding, insufficient legislation, a lack of professional involvement, a lack of infrastructure, a lack of strategic planning, uncivilized behavior, and demographics.…”
Section: Related Workmentioning
confidence: 99%
“…In 2022 Aiqin Wang et al., (Wang et al., 2022) determined how these policies will affect citizens' satisfaction with solid waste management services (SWMS) and the factors that influence it on a local and national level. They used Thought Works' application program Jinshuju to conduct an online poll regarding SWMS, and 1189 of the samples were usable.…”
Section: Literature Reviewmentioning
confidence: 99%